PENGARUH FLAS SALE, LIVE STREAMING DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK G2G MELALUI FREE ONGKIR SEBAGAI VARIABEL INTERVENING DI PLATFORM SHOPPE (Studi Kasus Pembelian Cushion G2G di Kabupaten Lamongan) - indramayu lindyawanti, Siti titis; Maulida, Indira Shofia (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2025)
Abstract This study aims to determine the effect of flash sales, live streaming, and brand image on the decision to purchase G2G (Glad 2 Glow) products on the Shopee platform, with free shipping as an intervening variable. The research questions in this study include how each variable, both directly and indirectly through free shipping, influences consumer purchasing decisions. The variables in this study include flash sales (X1), live streaming (X2), and brand image (X3) as independent variables, purchasing decisions (Y) as the dependent variable, and free shipping (Z) as the intervening variable. The population in this study consists of 3,500,000 followers of the official G2G shop on the Shopee platform, with a sample size of 125 respondents obtained using purposive sampling. The urgency of this study is driven by the intense competition in the online beauty industry, necessitating measurable digital marketing strategies to increase purchase conversion rates. This study uses a quantitative approach with a survey method, while data analysis techniques are conducted using Structural Equation Modelling (SEM) based on Partial Least Squares (PLS) through the SmartPLS 4.0 application. The results of the study indicate that flash sales, live streaming, and brand image have a positive and significant effect on purchase decisions, both directly and indirectly through free shipping. Free shipping was found to be a partial mediating variable that strengthens the relationship between independent variables and purchase decisions. The limitations of this study lie in its scope, which focuses on a single brand and a single e-commerce platform. The implications of this study suggest that integrating digital promotional strategies with logistical incentives such as free shipping can be an effective approach to increasing consumer purchase decisions in marketplaces. Keywords: Flash Sale, Live Streaming, Brand Image, Free Shipping, Purchase Decision, Shopee, G2G.